Geological Structures in The Formation of The Kendal Plains: Insights from Remote Sensing Imagery - Jamal, Jamal; Indra Sanjaya; Dian Hari Saputro; Aji Suteja (Pusat Survei Geologi, 2024)
Kendal Area in Central Java experiences rapid regional geology development. A wide flat area extending towards the Pantura, approximately 40 km wide and 20 km long, is influenced by the Bodri River. The Kendal basin formation is driven by Java’s regional compression tectonics. Major faults show the east-west direction as thrust faults and northeast-southwest direction as strike slip faults correspond to Java’s Regional Structures. Active and passive satellite imagery reveals geomorphic features such as deltas, coastal deposits, paleochannels, break slopes as faults zone, and topographic offsets of the area. The drainage pattern varies with deposit types: distributary channels in the north, meandering channels in the middle, and tributary channels in the south. Fusion image of Landsat 8 and National Digital Elevation Model (DEMNAS) produced by Badan Informasi Geospasial Indonesia (BIG) highlight distinct topographical boundaries and slopes. Residual gravity data shows subsurface contrasts, indicating dominant directions related to surface faults. Other supporting data used include magnetic anomaly imagery processed using the Reduce to Pole (RTP) method which are used to position the source of magnetic anomalies directly above their actual subsurface location. The RTP results enable more accurate interpretation of the distribution and depth of subsurface magnetic sources. The magnetic RTP model aligns with imagery, exhibiting east-west, northeast-southwest, and northwest-southeast trends. This structural interpretation is substantiated by field validation, with evidence of fault cliffs, lithologic offset, fault planes, mylonitization, and fault breccias corroborating the findings. Keywords: Bodri River, gravity, Kendal, landsat 8, Java’s regional structures, magnetic anomaly.